Board directors and corporate social responsibility - Boubaker, Sabri; Nguyen, Duc Khuong, 1978- (Houndmills, Basingstoke, Hampshire ; New York, NY : : Palgrave Macmillan, 2012)
"Boards of directors and corporate social responsibility (CSR) have been the subject of much study and debate in corporate governance circles over the two last decades. With issues ranging from poor corporate reporting to excessive executive compensation often splashed in the headlines, the role of boards comes into media limelight as never before. Boards of directors are also becoming increasingly aware of CSR issues. Besides, many listed and unlisted companies have put in place governance, ethics or CSR committees that prepare and recommend corporate governance rules, policies and practices to management and supervise their implementation. However, integrating CSR into the business strategy in a global market context and under financial market pressure might not be an easy task."--Back cover.
Part 1: Board directors. Women on Corporate Boards of Directors: Facts, Figures and Analysis / R. Dang & L.C. Vo ; How Successful are Women in Breaking the Glass Ceiling: Evidence from the US Market / T. Triki, H. Sami & L. Ureche-Rangau ; Governance by Boards and Audit Committees / G. Rioux ; Enhancing the Board's Monitoring Performance in SMEs / L. Karoui, W. Khlif, C. Ingley & S. Boubaker ; Corporate Governance: How do Non-profit Boards Influence Organizational Decisions? / J. Browning ; Supervisory Boards in Developing Economies: the Polish Experience / I. Koladkiewicz ; Corporate Governance Disclosures in Romania / M.M. Gi||rbina, N. Albu & C.N. Albu. -- Part 2: Corporate social responsibility. Corporate Governance as Social Responsibility: A Meta-regulation Approach to Raise Social Responsibility on Corporate Governance in Weak Econ-omy / M.M. Rahim ; Corporate Social Responsibility and Firms Ability to Collude / L. Lambertini & A. Tampieri ; Corporate Social Responsibility Rating Information: Relevance and Impacts on Financial Markets / A. Cellier & P. Chollet ; Corporate Social Responsibility and the Board's Role in Switzerland / P. Gantenbein & C. Volonte|| ; The Diffusion of Corporate Governance Standards in an Emerging Market: Evidence from Istanbul Stock Exchange / B. Ertuna & A. Tu||kel ; Corporate Socially Responsible Practice by Banks in Singapore / H. Ha ; When CSR Drives New Corporate Governance: Does the Latest French Law Reform (the 'Grenelle 2 Law') Confirm the End of 'Business as Usual'? / I. Tchotourian.
Includes bibliographical references and index.
Keywords: Social responsibility of business; Directors of corporations; Executives; Corporate governance; Corporate governance..; Directors of corporations..; Executives..; Social responsibility of business..; Responsabilite|| sociale des entreprises; Administrateurs de socie||te||s.; Chefs d'entreprise.; Gouvernement d'entreprise.